1999
DOI: 10.1177/096120339900800604
|View full text |Cite
|
Sign up to set email alerts
|

Do antibodies to β2-glycoprotein 1 contribute to the better characterization of the antiphospholipid syndrome?

Abstract: The aim of this study was to determine if the measurement of anti-beta2-glycoprotein I antibodies (abeta2-GPI) in serum levels contributes to the better characterization of the clinical situation of patients with antiphospholipid syndrome (APS). For this purpose abeta2-GPI of both isotypes was measured in 42 patients with APS and 32 SLE patients without APS. Clinical records of all patients were thoroughly reviewed. The presence of abeta2-GPI was correlated with the clinical manifestations of APS and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 33 publications
1
24
0
1
Order By: Relevance
“…Recent investigations addressing this issue [72,89,[102][103][104][105][106][107][108][109] found that multiple positivity in tests exploring the presence of aPL is more frequently associated with thromboembolic events and pregnancy morbidity than single-test positivity. Much of the controversy stems from the poor standardization of the laboratory detection procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations addressing this issue [72,89,[102][103][104][105][106][107][108][109] found that multiple positivity in tests exploring the presence of aPL is more frequently associated with thromboembolic events and pregnancy morbidity than single-test positivity. Much of the controversy stems from the poor standardization of the laboratory detection procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The OD units for each result were calculated on the basis of the standard curve. Samples with <10 GPL units, [10][11][12][13][14][15][16][17][18][19][20] Of the total patients, 19 were with low, moderate or high aCL-aPI antibody levels (Table I a aCL+; of the patients CA19.9 positive 37.5% was aCL+ and 62.5% aPI+; of the patients CEA-CA19.9 30% was aCL+ and 30% aPI+; of the patients CA125 positive 9% was aPI+; of the patients CEA-CA125 positive 100% was aPI+; of the patients CEA-CA15.3 25% was aCL+ and 25 aPI+ (Fig. 3).…”
Section: Igm- Igg-acl and Igm- Igg -Api Evaluationmentioning
confidence: 99%
“…Nevertheless, testing only for aCL antibodies does not always permit detection of all aPLs, especially when only IgG are evaluated. In fact, the majority of APS patients had aCL or lupus anticoagulant (LAC) antibodies, but some of them had only monospecific aPL antibodies, reacting against phosphatidylinositol and phosphatidylserine, which the conventional aCL assay fails to detect (17)(18). In the selected population of patients affected by deep venous thrombosis (DVT), moderate or high levels of antiphosphatidylinositol (aPI) and/or antiphosphatidylserine (aPS) antibodies, but no aCL antibodies, were found in 8.1% patients.…”
mentioning
confidence: 99%
“…monospecific aPL antibodies, reacting against PI and PS, which the conventional aCL assay fails to detect (8,9). The mechanism by which these antibodies are induced and the nature of the association of aPL with thrombosis is unknown.…”
mentioning
confidence: 99%